2015
DOI: 10.1007/s13277-015-3930-0
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 polymorphisms have an impact on the prognosis of Chinese diffuse large B cell lymphoma patients

Abstract: MDR1 (multidrug resistance 1) encodes an adenosine triphosphate (ATP)-dependent efflux transporter that plays a fundamental role in transportation of harmful compounds outside cells to maintain optimal health. The present study was aimed to investigate whether the MDR1 gene single nucleotide polymorphisms (SNPs) were associated with the prognosis of diffuse large B cell lymphoma (DLBCL). Three common SNPs, including C1236T, G2677T/A, and C3435T were focused on, and a total of 150 DLBCL patients from Jiangsu Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This study suggested that none of the alleles and genotypes at MDR1 C3435T was associated with the response of DLBCL to R-CHOP regimen, which was consistent with the study of Nizar M Mhaidat et al [ 11 ] While the study of Ying Ni et al [ 15 ] showed that DLBCL patients carrying C allele achieved better efficacy ( P = .009), whose mechanism may be siRNA-mediated down-regulation of ABCB1 (MDR1), thereby leading to the accumulation of chemotherapeutic agents in tumor cells to induce apoptosis. [ 19 ] The inconsistency of results may be related to the different grouping of efficacy in study design.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study suggested that none of the alleles and genotypes at MDR1 C3435T was associated with the response of DLBCL to R-CHOP regimen, which was consistent with the study of Nizar M Mhaidat et al [ 11 ] While the study of Ying Ni et al [ 15 ] showed that DLBCL patients carrying C allele achieved better efficacy ( P = .009), whose mechanism may be siRNA-mediated down-regulation of ABCB1 (MDR1), thereby leading to the accumulation of chemotherapeutic agents in tumor cells to induce apoptosis. [ 19 ] The inconsistency of results may be related to the different grouping of efficacy in study design.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism may be that molecules on the surface of tumor cells induce expression of G-protein-coupled receptors, which up-regulate the level of MDR1 and lead to the development of tumor drug resistance. [ 16 ] In contrast, the study of Ni Y et al [ 15 ] showed that C allele and CC genotype of C3435T were associated with a better prognosis in DLBCL. Our study did not get any statistically significant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 By contrast, some studies have shown that Chinese B cell lymphoma patients with the T allele of the ABCB1 C 1236 T polymorphism had an increased OS. 29 These discrepancies could be attributed to ethnicity, patient clinical features, and tumor histological heterogeneity, which could play an important role. However, many more studies are required to understand how the ABCB1 C 1236 T polymorphism affects MDR1 gene expression and its protein function.…”
Section: Discussionmentioning
confidence: 99%
“…), were found to be significantly upregulated. Indeed, MDR1 has been indicated to predict a poor prognosis in patients with DLBCL [26, 27]. However, the reason MDR1 is overexpressed in tumor tissues of treated patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%